Investigation of the antagonistic properties of Bacillus subtilis bacteria against carrot phytopathogens - T. V. Pershakova; S. M. Gorlov; L. V. Mikhailyuta; M. V. Babakina; G. A. Kupin (Новые технологии)
The IMP 215 strain of Bacillus subtilis has been studied for its potential use as a biological control agent for the Alternaria radicina and Botrytis cinerea phytopathogens of carrot during storage. In the presence of the IMP 215 strain of Bacillus subtilis the investigated phytopathogens slow the rate of development and reproduction on the wound surface of root crops. The obtained results allow to make a conclusion about the expediency of using the IMP 215 strain of Bacillus subtilis to reduce the incidence of root crops of carrots during storage.